Słuchająca „zamilkłych głosów” i jej opowieść. Myśl feministyczna Rachel Elior - Kornacka-Sareło, Katarzyna (Studia Europaea Gnesnensia, 2014)
The aim of this article is to present the feminist thought of Prof. Rachel Elior (the Hebrew University, Jerusalem), who is a world-known scholar working, mainly, in the field of Jewish mysticism in its different forms and aspects. Nevertheless, Prof. Elior dedicated some of her works also to the problem of Jewish women who, for centuries, have been, generally, absent, in social, religious and cultural life of Jewish communities living in different parts of the world. As the analysis of Elior’s feminist literature shows, the aforementioned absence of the women has been mainly caused by the patriarchal order, created “by men and for men”, by means of some male narratives and male mythology, in which women seem to be – usually - perceived as some inferior creatures or they are simply demonized.